ANTONIO ROSSANO MENDES PONTES, JOSÉ RAMON GADELHA, ÉVERTON R. A. MELO, FABRÍCIO BEZERRA DE SÁ, ANA CAROLINA LOSS, VILACIO CALDARA JUNIOR, LEONORA PIRES COSTA & YURI L. R. LEITE (2013) A new species of porcupine, genus Coendou (Rodentia: Erethizontidae) from the Atlantic forest of northeastern Brazil. Zootaxa, 3636(3): 421–438. - Pontes, Antonio Rossano Mendes; Gadelha, José Ramon; Melo, Éverton R. A.; de Sá, Fabrício Bezerra; Loss, Ana Carolina; Junior, Vilacio Caldara; Costa, Leonora Pires; Leite, Yuri L. R. (Zootaxa, 2013)
In Description, section Skull, on page 426, line 27: "fossa ?-shaped" should read "fossa V-shaped".